Анализ однонуклеотидных полиморфизмов генов MTHFR и MTRR у больных псориазом - Федота, А.М.; Рощенюк, Л.В.; Горайчук, И.В.; Тыжненко, Т.В.; Адмакина, А.В. (Фактори експериментальної еволюції організмів, 2016)
Aim. Analysis of single nucleotide polymorphisms C677T, A1298C and A66G of MTHFR and MTRR one-carbon metabolism genes in patients with various forms of psoriasis in Ukrainian population. Methods. A molecular genetic analysis of 77 patients with vulgaris and arthropathic psoriasis by PCR-RFLP was carried out. Results. In patients with vulgaris and arthropathic psoriasis analysis of the distribution of frequencies of genotypes showed a statistically significant difference between them for A66G and C677T polymorphic variants. In patients with psoriasis analysis of genotype distribution of series in the two genes as a whole, showed a statistically significant difference between the theoretically expected and actual frequencies for single nucleotide polymorphisms A1298T and A66G of MTHFR and MTRR genes. Conclusions. Among patients with arthropatic psoriasis, which is the most severe form of psoriasis, the homozygotes for the wild-type allele A of A66G of MTRR gene are more common, homozygotes of the TT of C667T of MTHFR gene are found more rarely than among psoriasis vulgaris patients, which may indicate the contribution of other genes to the development of arthropatic psoriasis. Keywords: psoriasis, arthropatic psoriasis, folate cycle, MTHFR gene, MTRR gene.